2023
DOI: 10.3390/catal13071137
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Catalysts for Conventional Oxidation of Alcohols: A Brief Review

Abstract: This review highlights recent research on the application of core–shell structured materials as catalysts in the oxidation of alcohols to value-added products, such as benzaldehyde, acetophenone, benzophenone, cinnamaldehyde, and vanillin, among others. While the application of various unconventional energy inputs (such as microwave and ultrasound irradiation) was reported, this paper focuses on conventional heating. The oxidation of homocyclic aromatic, heterocyclic aromatic, aliphatic, and alicyclic alcohols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In contrast, H 2 O 2 , TBHP (tert-butyl hydroperoxide) and O 2 are considered as green oxidants due to their environmental friendliness. Various heterogeneous catalysts based on noble metals (Pd, Au, Ru) or transition metals (Fe, Co, Zn, Ce, Cu, et al) have been reported for this reaction with green oxidants [7]. Zhang et al [8] synthesized a series of Pd/CeO 2 catalysts by exposing different crystal facets of the CeO 2 support and successfully activated O 2 for benzyl alcohol selective oxidation by the most abundant oxygen vacancies and optimized metal-support interaction on the CeO 2 (110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, H 2 O 2 , TBHP (tert-butyl hydroperoxide) and O 2 are considered as green oxidants due to their environmental friendliness. Various heterogeneous catalysts based on noble metals (Pd, Au, Ru) or transition metals (Fe, Co, Zn, Ce, Cu, et al) have been reported for this reaction with green oxidants [7]. Zhang et al [8] synthesized a series of Pd/CeO 2 catalysts by exposing different crystal facets of the CeO 2 support and successfully activated O 2 for benzyl alcohol selective oxidation by the most abundant oxygen vacancies and optimized metal-support interaction on the CeO 2 (110) surface.…”
Section: Introductionmentioning
confidence: 99%